2010
DOI: 10.1007/s10059-010-0081-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of isolated from murine adult tissues very small embryonic/epiblast like stem cells (VSELs)

Abstract: Pluripotent very small embryonic/epiblast derived stem cells (VSELs) as we hypothesize are deposited at begin of gastrulation in developing tissues and play an important role as backup population of pluripotent stem cells (PSCs) for tissue committed stem cells (TCSCs). We envision that during steady state conditions these cells may be involved in tissue rejuvenation and in processes of regeneration/repair after organ injuries. Molecular analysis of adult bone marrow (BM)-derived purified VSELs revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 31 publications
5
55
0
1
Order By: Relevance
“…The expression of these genes suggests that HERS/ERM cells might contain more primitive stem cell characteristics. Recently, the possibility that adult stem cells (ASCs) may contain populations of cells with varying degrees of stemness has been suggested (Shin et al, 2010;Stripp, 2008;Verstappen et al, 2009). The hierarchi-cal organization of stem cells was described for various organs and tissues including the breast, intestine, limbus, lung, skin, and intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of these genes suggests that HERS/ERM cells might contain more primitive stem cell characteristics. Recently, the possibility that adult stem cells (ASCs) may contain populations of cells with varying degrees of stemness has been suggested (Shin et al, 2010;Stripp, 2008;Verstappen et al, 2009). The hierarchi-cal organization of stem cells was described for various organs and tissues including the breast, intestine, limbus, lung, skin, and intestine.…”
Section: Discussionmentioning
confidence: 99%
“…S1) and this may possibly reflect presence of abundant euchromatin in them, since DAPI is understood to preferentially stain heterochromatin [27,28]. Similarly, the flow sorted very small embryonic-like stem cells (VSELs) isolated from various adult tissues, always stain much lighter with DAPI as compared to hematopoietic stem cells during the gating experiments reported by Ratajczak et al [29][30][31], personal communication with Dr Ratajczak's group]. Pluripotent markers also showed differential staining pattern in the 2 populations of PSCs.…”
Section: Pscs In Osementioning
confidence: 98%
“…We found at least three different types of libraries generated from single, sorted VSELs, and some of these libraries exhibited a strong epiblast-or PGC-like gene expression pattern. In support of such a connection, we observed that murine BM-derived VSELs express several genes that are characteristic of epiblast SCs (Gbx2, Fgf5, and Nodal) and, more importantly, of germline specification and migrating PGCs (Stella, Prdm14, Fragilis, Blimp1, Nanos3, and Dnd1) [64,65]. The expression of some of these crucial genes has subsequently been confirmed by demonstrating the presence of transcriptionally active promoters in these genes.…”
Section: Question 2 -Do Early-development Stem Cells Reside In Adult mentioning
confidence: 56%